Psychological Response to Chemotherapy: The Association Between Treatment Related Side Effects and Anxiety in Breast Cancer Patients - Hayatus Sa’adah Ayu Lestari; Yuza Olsi Rahmi; Tsuwaibatul Islamiyah; Rifda Nur Achriyana Arif; Muthmainnah Muthmainnah; Yohana Agustina; Priska Ekayanti Mahdiansyah (Universitas Pahlawan Tuanku Tambusai, 2026)
Anxiety is a common emotional response among patients undergoing chemotherapy and may influence treatment adherence and quality of life. Understanding the association between chemotherapy side effects and anxiety is essential to support comprehensive cancer care. This study aimed to analyze the relationship between chemotherapy side effects and anxiety in breast cancer patients undergoing chemotherapy. This study employed a quantitative correlational method with a cross-sectional design. The research was conducted at Bangil Regional Hospital from November to December 2022. A total of 104 female breast cancer patients undergoing chemotherapy were selected using purposive sampling based on inclusion and exclusion criteria. Data were collected using two instruments: a chemotherapy side effects questionnaire adapted from Portenoy et al. (1994), and the Zung Self-Rating Anxiety Scale (SAS). The data were analyzed using spearman’s rank correlation. Chemotherapy side effects were predominantly classified in the mild category, with 66 respondents (63.5%) meanwhile, anxiety levels were mostly within the normal range, as reported by 68 respondents (65.4%). Spearman rank correlation analysis demonstrated a statistically significant positive relationship between chemotherapy side effects and anxiety (ρ = 0.335, p = 0.001). There is a statistically significant positive relationship between chemotherapy side effects and anxiety levels among breast cancer patients undergoing chemotherapy, indicating that greater severity of chemotherapy side effects is associated with higher levels of patient anxiety